Carbon coated "zero-strain" Li2TiSiO5 nanowires for high-performance lithium storage. (31st December 2023) - Gao, Shangfu; Li, Songjie; Gao, Jiazhe; Liu, Xuehua; Lin, Chunfu
ABSTRACT: Li2 TiSiO5 is a 'zero-strain' anode material with a large theoretical capacity, appropriate operation potential, and good cyclability. However, its low electronic conductivity negatively affects its practical capacity and rate performance. Herein, we improve the electrochemical performance of Li2 TiSiO5 by carbon-coating and nanosizing dual modifications, and further explore its lithium-storage and 'zero-strain' mechanisms by in-situ XRD. Within 0.2–3.0 V, the carbon-coated Li2 TiSiO5 nanowires deliver a large reversible capacity of 257 mAh g −1, high rate performance with a 5000 mA g −1 vs. 50 mA g −1 capacity ratio of 71.6%, and excellent cyclability with 90.0% capacity retention at 5000 mA g −1 over 4000 cycles. The special crystal structure of Li2 TiSiO5 with electrochemical active TiO6 octahedra surrounded by inactive SiO4 and LiO6 polyhedra can effectively strengthen the volume-buffering capability, resulting in the 'zero-strain' behaviour with a tiny lattice-volume change of only 0.41%. Therefore, this dual-modified Li2 TiSiO5 material has great practicability for high-performance lithium storage.